Non-polynomial framework for static analysis of functionally graded carbon nano-tube reinforced plates. (1st February 2020) - Soni, Aakash; Grover, Neeraj; Bhardwaj, Gagandeep; Singh, B.N.
Abstract: The reinforcement in the form of carbon nano-tubes (CNTs) enhances the bending response of the structures. The bending characteristics are altered due to functionally graded distributions of CNTs. The bending behaviour of functionally graded CNTs reinforced plates is carried out in the present work. The carbon nano-tubes are supposed to be distributed uniformly and graded functionally. The reinforced plates are modelled for the first time in the framework of inverse hyperbolic shear deformation theory. The governing equations of the plate are obtained using the principle of virtual work under the assumptions of linear kinematics and generalised Hooke's law. These governing equations are solved in the closed form using Navier solution for specific boundary conditions i.e. simply supported. The static response of these plates are obtained under the effect of sinusoidal load, uniform load, hydrostatic load, and central point load. The computed results are compared with some of the existing results for a few cases to ensure the validity. Further, the effects of parameters such as CNT volume fraction, orientation of reinforcement, span-thickness ratio, loading conditions, etc. on the static response characteristics are examined in details and various conclusions are observed.